The Influence of Brand Image, Trust, Electronic Word of Mouth On Consumer Loyalty of Jambi Typical Souvenirs (Outlet Temphoyac) - Akhmad Irwansyah Siregar; Riko Mappadeceng; Albetris Albetris (Universitas Batanghari Jambi, 2021)
This research was conducted to look at the influence of Brand Image Trust, and eWOM on Loyalty at the center of souvenirs typical of Jambi. The study was conducted on 100 consumers of The Typical Souvenir Center of Jambi (Temphoyac outlet) with purposive sampling method, and analyzed using the SPSS program. The results of research known to Trust, Brand Image and eWOM significantly affect loyalty, with brand image having a negative relationship to loyalty and trust variables and EWom having a positive relationship to loyalty.